FUNGSI GRAMATIKAL FRASA NUMERALIA DALAM KAMUS DWIBAHASA: BAHASA MOOI-BAHASA INDONESIA - Azka, Mazida Izzatul; Argandari, Rozana (Prosiding Seminar Nasional Bahasa Ibu, 2025)
Numeralia phrases in the Mooi language are one of the phrases that Papuans often use in the Jayapura Regency because of their crucial function in daily life. However, few studies have been conducted on the Mooi language, especially its grammatical phrases. Therefore, this research aims to find the grammatical function of numeral phrases (Fnum) in the Mooi language. The type of research used is descriptive qualitative research with morphosyntactic studies. The data of this research are clauses and sentences containing numeralia phrases (Fnum) in the Bilingual Dictionary: Mooi-Indonesian. The data were collected using searching and note-taking techniques. This research also used the distributional method. The research findings show that the grammatical function of numeral phrases in the Mooi language has three functions: subject, predicate, and Object. From the findings above, the numeral phrases are distributed significantly in the Mooi language. This shows that numeral phrases are not only numbers but also have an important role in the readability and comprehension of Mooi.